2012
DOI: 10.5897/ajb11.2783
|View full text |Cite
|
Sign up to set email alerts
|

Multi-drug resistance and molecular pattern of erythromycin and penicillin resistance genes in Streptococcus pneumoniae

Abstract: The appearance and dissemination of penicillin resistant and macrolide resistant Streptococcus pneumoniae strains has caused increasing concern worldwide. The aim of this study was to survey drug resistance and genetic characteristics of macrolide and penicillin resistance in S. pneumoniae. This is a cross-sectional study, which was carried out on 70 samples suspected to be S. pneumoniae isolated from patients who were admitted in Intensive Care Unit (ICU) of southwest of Iran, in 2010 and 2011. At first, susp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…strains isolated from different hospital infections (Malhotra-Kumar et al 2005;Zeng et al 2006;Xu et al 2010). Kargar et al (2012) reported the high prevalence of ermB, mefA, pbp1a, pbp2b and pbp2x genes in the S. pneumonia strains isolated from different types of the hospital infections of hospitalized patients in the Intensive Care Unit (ICU) centers. Presence of these genes in the Streptococcus spp.…”
Section: Discussionmentioning
confidence: 99%
“…strains isolated from different hospital infections (Malhotra-Kumar et al 2005;Zeng et al 2006;Xu et al 2010). Kargar et al (2012) reported the high prevalence of ermB, mefA, pbp1a, pbp2b and pbp2x genes in the S. pneumonia strains isolated from different types of the hospital infections of hospitalized patients in the Intensive Care Unit (ICU) centers. Presence of these genes in the Streptococcus spp.…”
Section: Discussionmentioning
confidence: 99%
“…strains isolated from different hospital infections [32][33][34]. Kargar et al (2012) [35] reported the high prevalence of ermB, mefA, pbp1a, pbp2b and pbp2x genes in the S. pneumonia strains isolated from different types of the hospital infections of hospitalized patients in Intensive Care Unit (ICU) centers. Presence of these genes in the Streptococcus spp.…”
Section: Discussionmentioning
confidence: 99%